The Teachers’ Responses to Curriculum Changes in Indonesia - Cindy Eka Pratiwi; Rislianta Alsabila; Vilda Eka Febrianti; Evia Anita Sari; M. Fery Abdillah; Dimas Abdul Rozaq (Basic and Applied Education Research Journal, 2020)
Curriculum changes in Indonesia are made to adapt to the times. In the 21st century, the quality of learning must be related to students' analytical skills. This study aimed to analyze teacher responses to curriculum changes in Indonesia. The method used was a survey. Research subjects or respondents consisted of school principals, two students in each school, and teachers. Interviews were conducted with principals, vice-principals, teachers, and students, while the teacher also fills in a closed questionnaire prepared previously. The analysis used is descriptive, which is assisted by a percentage. The results show that the teacher's response does not match the characteristics of the new curriculum. The characteristics of the new curriculum consist of aspects of learning methods. In this aspect the majority of teachers use the lecture method, while the new curriculum recommends the discovery method. In the media aspect, the majority of teachers do not use learning media optimally. In learning outcomes, students' abilities can only be measured in aspects of remembering and understanding. The teacher cannot respond directly to curriculum changes. The teacher's methods and media must follow the new curriculum's character so that students' analytical skills in the curriculum can be measured optimally.